Symbolic Interaction Analysis of The Baayun Maulid Tradition of The Banjar Community - Arif Sugian; Ady Muh. Zainul Mustofa (MKWK PAI Universitas Jambi, 2023)
The Baayun Maulid tradition is a religious celebration specifically practised by the Banjar community in the month of Rabi'ul Awwal or what is commonly referred to as the